Pleomorphic adenoma of the salivary glands with intravascular tumor deposits: a diagnostic pitfall - Skalova, Alena; Altemani, Albina; Di Palma, Silvana; Simpson, Roderick H W; Hostička, Lubor; Andrle, Pavel; Laco, Jan; Toner, Mary; Vozmitsel, Marina A; Szakacs, Susan; Kazakov, Dmitry V; Kinkor, Zdeněk; et al. (The American journal of surgical pathology, 2012)
The diagnosis of pleomorphic adenoma (PA) of salivary glands is usually straightforward posing few diagnostic problems for the general surgical histopathologist. The purpose of our investigation was to present a series of 22 cases of PA of major salivary glands, each of which contained small foci of tumor within vascular spaces. This feature has previously been described very rarely in PA and may represent a significant diagnostic pitfall. The patients included 12 women and 10 men, ranging in age at diagnosis from 17 to 82 years. Histopathologically, all 22 tumors displayed the features of PA with mixed epithelial and myoepithelial growth patterns and chondromyxoid areas. None of these neoplasms showed any cytologic evidence of malignancy. In all cases, there were multiple dilated thin-walled and/or muscular thick-walled blood vessels containing small intraluminal collections of neoplastic cells with or without myxoid stromal components. The intravascular tumor cells expressed cytokeratins, and in some cases they were also immunoreactive for S-100 protein, GFAP, D2-40, and p63 protein. The intravascular location of the neoplastic cells was confirmed by CD31, CD34, and factor VIII-related antigen immunostains. Reaction for D2-40 was negative in the endothelium of the involved vessel in all cases, confirming that they were vascular rather than lymphatic channels. Seven patients (36%) underwent fine-needle aspiration biopsy 25 days to several years before excision of the tumor. Follow-up of the patients in our series revealed no cases of recurrence or metastasis (range, 6 mo to 9.5 y; mean 3.8 y; median 3.5 y). The biological significance of intravascular tumor in PA is not clear, but there is growing evidence that it is an innocuous phenomenon that might be related to artifactual spillage caused by tumor injury presumably by either fine-needle aspiration or intraoperative trauma.
Keywords: senioři; diferenciální diagnóza; vaskulární nádory; Diagnostic Errors; von Willebrandův faktor; senioři nad 80 let; Submandibular Gland Neoplasms; mladiství; nádory podčelistní slinné žlázy; antigeny CD31; Middle Aged; Biopsy, Fine-Needle; mužské pohlaví; Antigens, CD34; Adult; mladý dospělý; Adolescent; Biomarkers, Tumor; Aged, 80 and over; Artifacts; Vascular Neoplasms; Young Adult; Disease-Free Survival; tenkojehlová biopsie; ženské pohlaví; nádorové biomarkery; Parotid Neoplasms; Humans; artefakty; chybná diagnóza; pleomorfní adenom; nádory příušní žlázy; lidé středního věku; von Willebrand Factor; Platelet Endothelial Cell Adhesion Molecule-1; Diagnosis, Differential; dospělí; antigeny CD34; Female; Aged; Adenoma, Pleomorphic; přežití bez známek nemoci; lidé; Male